1984
DOI: 10.2519/jospt.1984.5.4.184
|View full text |Cite
|
Sign up to set email alerts
|

Hamstrung by Hamstring Strains: A Review of the Literature

Abstract: The purpose of this paper is to review those studies which have attempted to delineate causative factors of hamstring strains. Anatomy and biomechanics of the hamstring muscle group are reviewed. Mechanisms of injury and various etiological factors are presented. Decreased hamstring muscle flexibility and decreased hamstring muscle strength were factors most frequently studied, yet the relationship of these factors to the incidence of hamstring strains remains unclear. Future studies should seek to test hamstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 15 publications
0
19
0
2
Order By: Relevance
“…Cameron et al 12 suggested that sportspeople with lower movement discrimination scores had an increased risk for incurring a hamstring injury 12. The earlier onsets of the hamstring-injured muscles during the double- to single-leg may reflect changed proprioception39 following an injury of the hamstring muscle. From a clinical perspective, patients with a history of hamstring injuries often complain of persistent feelings of discomfort or tightness in their hamstrings which prevent them from reattaining full preinjury training levels 3942.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cameron et al 12 suggested that sportspeople with lower movement discrimination scores had an increased risk for incurring a hamstring injury 12. The earlier onsets of the hamstring-injured muscles during the double- to single-leg may reflect changed proprioception39 following an injury of the hamstring muscle. From a clinical perspective, patients with a history of hamstring injuries often complain of persistent feelings of discomfort or tightness in their hamstrings which prevent them from reattaining full preinjury training levels 3942.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier onsets of the hamstring-injured muscles during the double- to single-leg may reflect changed proprioception39 following an injury of the hamstring muscle. From a clinical perspective, patients with a history of hamstring injuries often complain of persistent feelings of discomfort or tightness in their hamstrings which prevent them from reattaining full preinjury training levels 3942. These symptoms may be present beyond the time frame normally considered to be necessary for healing of myotendinous structures.…”
Section: Discussionmentioning
confidence: 99%
“…lnjuries associated with a lack of flexibility or abnormal mobility such as -joint hypo/hypermobility (i.e., hip, superior tibiofibular) (4,29,30,45). 3) lnjuries due to variables associated with the training program which include -poor conditioning -overtraining/fatigue -overstretching, etc.…”
Section: )mentioning
confidence: 99%
“…The causes of many of these athletic injuries have been shown to be of a non-contact nature 1) . Therefore, many factors such as lack of flexibility, loss of muscle strength, imbalance of antagonists, muscle fatigue, and lack of sufficient warm-up exercises have been reported as causes of hamstring strain [2][3][4][5][6][7] . Although there have been many reports on the development of symptoms of hamstring strain, none of these studies h a v e c a r r i e d o u t c o g n i t i v e n e u r o s c i e n c e examinations.…”
Section: Introductionmentioning
confidence: 99%